Evaluasi Penerapan Standard Mutu dan Keamanan Pakan Ayam Pedaging dengan Metode Analytic Network Process (ANP): Evaluation of the Implementation of Quality and Safety Standards for Broiler Feed Using the Analytic Network Process (ANP) Method - Irham, Ilda; Wijayanti, Indah; Retnani, Yuli; Risyahadi, Sazli Tutur (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2023)
This study aimed to evaluate the role of broiler feed standards using the Analytic Network Processing (ANP) method. Data were taken from five feed manufacturing companies, three feed experts and three government institutions in the feed sector. There were 3 criteria and 6 sub-criteria in determining the best alternatif out of 6 feed evaluation in the context of implementing broiler feed quality and safety standards. The results showed that the greatest sub-criteria weight was effectiveness (0.750). In addition, the selected alternatif analysis with the highest weight was proximate analysis (0.315; 0.280) in the assessment by feed companies and the government and followed by amino acids analysis (0.365) in the assessment by feed experts. From the results, all entities assessed the proximate analysis as a priority because proximate testing on animal feed could help to determine the nutritional quality of feed by knowing the content of protein, fat, crude fiber, and other nutrients in the feed. This study was concluded that proximate testing was very important in the animal feed industry because it could help in determining the nutritional quality of animal feed, optimizing livestock growth and production, preventing nutritional deficiencies in livestock, determining the selling price of feed, and guaranteeing feed quality. Key words: ANP, feed quality and safety testing, feed standards, quality control and feed safety